Essays in medical ethics : plea for a medicine of prudence - Maio, Giovanni (Thieme, 2017)
Modern medicine suggests omnipotence and an image of life as something that can be perfected at any time. Yet our view of things changes when disease throws us into an existential crisis. Then we seek human answers and feel misunderstood and abandoned in the system of modern medicine. Professor Giovanni Maio, the eloquent advocate of a new culture of medicine, poses fundamental questions in this book that no one can really avoid: Where are the promises of reproductive and transplantation medicine leading us? To what extent can health be made, and to what extent is it a gift? Does "prettier, better, stronger" promise us greater happiness? Why is the question of organ donation more difficult than is suggested to us? Does being old have its own intrinsic value? How can we acquire an attitude towards dying that does not leave us feeling powerless? Giovanni Maio's profound plea for an ethics of prudence opens up hitherto unknown perspectives. In this way we could free ourselves from the belief in perfection and find our way to a new serenity as a condition for a good life.